Wolbachia Acquisition by Drosophila yakuba-Clade Hosts and Transfer of Incompatibility Loci Between Distantly Related Wolbachia. Issue 4 (21st June 2019) - Cooper, Brandon S; Vanderpool, Dan; Conner, William R; Matute, Daniel R; Turelli, Michael
Abstract: Maternally transmitted Wolbachia infect about half of insect species, yet the predominant mode(s) of Wolbachia acquisition remains uncertain. Species-specific associations could be old, with Wolbachia and hosts codiversifying ( i.e., cladogenic acquisition), or relatively young and acquired by horizontal transfer or introgression. The three Drosophila yakuba -clade hosts [( D. santomea, D. yakuba ) D. teissieri ] diverged ∼3 MYA and currently hybridize on the West African islands Bioko and São Tomé. Each species is polymorphic for nearly identical Wolbachia that cause weak cytoplasmic incompatibility (CI)–reduced egg hatch when uninfected females mate with infected males. D. yakuba -clade Wolbachia are closely related to w Mel, globally polymorphic in D. melanogaster . We use draft Wolbachia and mitochondrial genomes to demonstrate that D. yakuba -clade phylogenies for Wolbachia and mitochondria tend to follow host nuclear phylogenies. However, roughly half of D. santomea individuals, sampled both inside and outside of the São Tomé hybrid zone, have introgressed D. yakuba mitochondria. Both mitochondria and Wolbachia possess far more recent common ancestors than the bulk of the host nuclear genomes, precluding cladogenic Wolbachia acquisition. General concordance of Wolbachia and mitochondrial phylogenies suggests that horizontal transmission is rare, but varying relative rates of molecular divergence complicate chronogram-based statistical tests. Loci that cause CI in w Mel are disrupted in D. yakuba -clade Wolbachia ; but a second set of loci predicted to cause CI are located in the same WO prophage region. These alternative CI loci seem to have been acquired horizontally from distantly related Wolbachia, with transfer mediated by flanking Wolbachia -specific ISWpi1 transposons.